2010
DOI: 10.1111/j.1442-2042.2010.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvage chemotherapy with methotrexate, etoposide and actinomycin D in men with metastatic nonseminomatous germ cell tumors with a choriocarcinoma component: A preliminary report

Abstract: Abstract:The objective of the present study was to assess the use of salvage chemotherapy using methotrexate, etoposide and actinomycin D (MEA) in men with nonseminomatous germ cell tumor (NSGCT) with a choriocarcinoma component. Nine patients were included. They had initially received bleomycin, etoposide and cisplatin, and high-dose ifosfamide, carboplatin and etoposide as induction chemotherapies. However, they failed to achieve the normalization of b-human chorionic gonadotropin (b-HCG). Therefore, MEA the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Actinomycin D (Dactinomycin, actD), an antitumor antibiotic inhibiting transcription, is one of the oldest chemotherapy drug used to treat various cancer types [Ward, ; Terakawa et al, ]. Pharmacokinetic studies of actD reported a median plasma concentration about 100 ng/ml (i.e., 80 nM) [Hill et al, ].…”
mentioning
confidence: 99%
“…Actinomycin D (Dactinomycin, actD), an antitumor antibiotic inhibiting transcription, is one of the oldest chemotherapy drug used to treat various cancer types [Ward, ; Terakawa et al, ]. Pharmacokinetic studies of actD reported a median plasma concentration about 100 ng/ml (i.e., 80 nM) [Hill et al, ].…”
mentioning
confidence: 99%
“…Several DNA intercalating drugs have been identified over the years, which include daunomycin (trade name Cerubidine), doxorubicin (trade name Adriamycin), epirubicin (anthracycline family), dactinomycin (trade name Cosmegen), ditercalinium, bleomycin, elsamicin A, m-AMSA, mitoxantrone, acridines, ethidium bromide and so on ( Fig. 14 ) [ 30 , 148 151 ]. Anthracyclines are a class of antitumor antibiotics, isolated from Streptomyces species, mostly used in various cancer chemotherapy such as acute leukemia, Hodgkin’s and non-Hodgkin’s lymphoma, breast and ovarian cancer, lung cancer, gastric (stomach) cancer, testicular cancer, bladder cancer and soft tissue sarcoma etc.…”
Section: Reviewmentioning
confidence: 99%
“…, 2010a,b). A Japanese group of investigators very recently demonstrated that the use of a combination regimen of methotrexate, etoposide and actinomycin D could be an option after failure to HDCT as a salvage chemotherapy for patients with a choriocarcinoma component in their tumours (Terakawa et al. , 2010).…”
Section: Management Of Patients With Multiply Relapsed or Cisplatin‐rmentioning
confidence: 99%
“…In a group of 76 heavily pre-treated relapsed patients, including patients previously treated with HDCT (78%) or showing cisplatin-refractory disease (73%), a PFS of 17 and 3% was seen after a 2 year follow-up among the patients treated with the combination of gemcitabine, oxaliplatin and paclitaxel (GOP), or gemcitabine and oxaliplatin, respectively (Oechsle et al, 2010a,b). A Japanese group of investigators very recently demonstrated that the use of a combination regimen of methotrexate, etoposide and actinomycin D could be an option after failure to HDCT as a salvage chemotherapy for patients with a choriocarcinoma component in their tumours (Terakawa et al, 2010).…”
Section: Management Of Patients With Multiply Relapsed or Cisplatin-rmentioning
confidence: 99%